French Colonial Louisiana and the Atlantic World - Bond, Bradley G., 1963- (Book collections on Project MUSE., 2005)
"French colonial Louisiana has failed to occupy a place in the historic consciousness of the United States, perhaps owing to its short duration (1699-1762) and its standing outside the dominant narrative of the British colonies in North America. This anthology seeks to locate early Louisiana in its proper place, bringing together a broad range of scholarship that depicts a complex and vibrant sphere."--Jacket